Groundwater situation before production and after production stoppage in Al-Mishraq Sulfur field-1, northern Iraq - Ali, Mohammed Abdilfattah; Salih, Sabbar Abdullah; Hussain, Amera Ismail (Iraqi Journal of Science, 2023)
This study dealt with the reality of groundwater before Sulfur production in the Al-Mishraq field-1 and after production stopped in the field, by measuring the groundwater table for (44) wells in 2021, and comparing it to the groundwater table measured by the Polish company Centrozap in 1971, the groundwater table was a range between (187.71-205.8)m in 1971, but in 2021 it ranged was between (188.51-196.55)m.Maps of the groundwater movement and water table were created using these data. It turned out that there was little change in the direction of groundwater flow; in both cases, the flow is from the west and northwest towards the east with a slight slope toward the southeast and the Tigris River. As for hydraulic properties, it was analyzed in (29) wells, depending on pumping test data from the reports of Al-Mishraq, It was noted that the values of Transmissivity ranged between (1557.5-24.4) m2/day before production and (5020.6-39.4) m2/day after production, As for hydraulic conductivity, it ranged between (0.26-14.68) m/day before production, and after production, it was between (0.4-48.9) m/day.